Use of Molding Mixtures for the Production of Cast Porous Metals - Ivana Kroupová; Martina Gawronová; Petr Lichý; Václav Merta; Filip Radkovský (Metals, 2022)
This paper aims to present the possibility of producing cast porous metals (or metallic foams) in a low-tech way by the use of conventional foundry technologies, i.e., the common procedures and materials. Due to the technological and economic complexity of the production processes of cast metallic foams, research into this material currently focuses on the development of less demanding technologies. The introduction of such production processes may help to exploit the full application potential of metallic foams. Within the framework of our proposed procedure, molding and core mixtures are used for the production of molds and filler material (space holder), also called precursors. It is the shape, size, and relative position of the individual precursors that determines the shape of the internal structure of the resulting metallic foam. The core mixture for the production of precursors is evaluated in terms of changes in properties with respect to storage time. Attention is focused on one of the most common bonding systems, furan no-bake. Casting tests are carried out for the possibility of making cast porous metals from aluminum alloy with different shapes of internal cavities depending on the different shapes of the filler material. The collapsibility of the cores after casting is evaluated for the test castings. The results show that even using commonly available materials and processes, cast metallic foams with complex internal structures can be produced.